MEDIA SIBEDA BERBASIS AUGMENTED REALITY MENGGUNAKAN LC5E MATERI PERUBAHAN WUJUD BENDA UNTUK MENINGKATKAN SELF-AUTHENTICITY DAN ADVERSITY QUOTIENT SISWA KELAS IV SEKOLAH DASAR - Muqtafa, Muhammad Afifuddin; Fatih, Mohamad; Alfi, Cindya (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of this research is to develop augmented reality-based Sibeda Media (Object Shape Transformation) using LC5E on material object shape transformation to increase the self-authenticity and adversity quotient of Class IV students. The approach applied in this research is Research and Development (R&D) with steps in developing the ASSURE model. The field experimental design used was a one group pretest-posttest design. Based on the research results, it is known that the media validity score by media experts achieved 98%, while material experts gave a score of 96%, both of which were categorized as very valid. While, teacher responses to the feasibility aspect achieved 97.5%, with a very feasible category. Based on student responses, Sibeda media based on augmented reality using LC5E received positive results, namely being able to be effective with a significant influence in increasing self-authenticity in the high category based on the average N-gain score reaching 0.767, and the results of the paired t-test showed significance. with Sig value. (2-tailed) of 0.000 < 0.05. Likewise, this product is also able to be effective with a significant effect in increasing the adversity quotient in the high category of students which is based on an average N-gain score of 0.768 and the results of the paired t-test get significant criteria with Sig. (2-tailed) is 0.000 < 0.05.